2013
DOI: 10.1186/1742-4933-10-29
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and chemokine responses to helminth and protozoan parasites and to fungus and mite allergens in neonates, children, adults, and the elderly

Abstract: BackgroundIn rural sub-Saharan Africa, endemic populations are often infected concurrently with several intestinal and intravascular helminth and protozoan parasites. A specific, balanced and, to an extent, protective immunity will develop over time in response to repeated parasite encounters, with immune responses initially being poorly adapted and non-protective. The cellular production of pro-inflammatory and regulatory cytokines and chemokines in response to helminth, protozoan antigens and ubiquitous alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 52 publications
1
9
0
3
Order By: Relevance
“…With repeated exposure to Plasmodium spp. and immune maturation, adequate and regulatory cytokine and chemokine responses may set off cellular effector mechanisms which will not induce severe infl ammation and which will avoid excessive host tissue and organ damage [16]. Recent stud-ies have shown that, in children with P. falciparum malaria, the profi le of cytokine and chemokine levels varied with disease severity; moreover, the proinfl ammatory chemokines MIP-1α/CCL3, MIP-1β/CCL4, and MIG/ CXCL9 and cytokines IL-31 and IL-33 were elevated, while RANTES/CCL5 and IL-27 appeared suppressed in children with severe falciparum malaria [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…With repeated exposure to Plasmodium spp. and immune maturation, adequate and regulatory cytokine and chemokine responses may set off cellular effector mechanisms which will not induce severe infl ammation and which will avoid excessive host tissue and organ damage [16]. Recent stud-ies have shown that, in children with P. falciparum malaria, the profi le of cytokine and chemokine levels varied with disease severity; moreover, the proinfl ammatory chemokines MIP-1α/CCL3, MIP-1β/CCL4, and MIG/ CXCL9 and cytokines IL-31 and IL-33 were elevated, while RANTES/CCL5 and IL-27 appeared suppressed in children with severe falciparum malaria [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study none of the participating children was infected with Ascaris lumbricoides and it should be considered that hookworm and S. haematobium and S. mansoni infections will cause intestinal and urinary tract tissue damage resulting in bloody urines and mostly occult blood in stools; these helminthes will always cause gastrointestinal inflammation. As previously observed, in infants and children with helminth and protozoa infections regulatory cytokine and chemokine responses were not evolved to levels as observed in adults [ 40 ], and such immune response profiles may develop with ageing and repeated episodes of exposure and persistent parasite infections. In the present study, allergen-specific positive skin prick test (SPT) responses were more frequent in co-infected children than in infection-free pupils suggesting that parasite co-infections may have triggered or even amplified pro-inflammatory reactivity to allergens.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly M. perstans is, however, considered one of the most prevalent human diseases in tropical areas with approximately 114 million infected people [ 1 , 2 , 18 ]. Most of the knowledge about M. perstans infection has been obtained as a by-product of studies with other filarial or parasitic infections [ 19 22 ] that were considered to be more important for public health. However, M. perstans -induced symptoms such as subcutaneous swellings, abdominal pain, skin rashes, pericarditis and pleuritis [ 1 , 2 ] have been reported.…”
Section: Discussionmentioning
confidence: 99%